The Role of TSC1 in the Macrophages Against Vibrio vulnificus Infection - Huang, Xian-Hui; Ma, Yao; Lou, Han; Chen, Na; Zhang, Ting; Wu, Liu-Ying; Chen, Yi-Ju; Zheng, Meng-Meng; Lou, Yong-Liang; Xie, Dan-Li (Frontiers in Cellular and Infection Microbiology, 2021)
Vibrio vulnificus (V. vulnificus) is an estuarine bacterium that is capable of causing rapidly fatal infection in humans. Proper polarization and bactericidal activity of macrophages play essential roles in defending against invading pathogens. How macrophages limit V. vulnificus infection remains not well understood. Here we report that tuberous sclerosis complex 1 (TSC1) is crucial for the regulation of V. vulnificus-induced macrophage polarization, bacterial clearance, and cell death. Mice with myeloid-specific deletion of TSC1 exhibit a significant reduction of survival time after V. vulnificus infection. V. vulnificus infection induces both M1 and M2 polarization. However, TSC1 deficient macrophages show enhanced M1 response to V. vulnificus infection. Interestedly, the absence of TSC1 in myeloid cells results in impaired bacterial clearance both in vivo and in vitro after V. vulnificus infection. Inhibition of the mammalian target of rapamycin (mTOR) activity significantly reverses V. vulnificus-induced hypersensitive M1 response and resistant bactericidal activity both in wild-type and TSC1-deficient macrophages. Moreover, V. vulnificus infection causes cell death of macrophages, possibly contributes to defective of bacterial clearance, which also exhibits in a mTORC1-dependent manner. These findings highlight an essential role for the TSC1-mTOR signaling in the regulation of innate immunity against V. vulnificus infection.